CONSIDERING MURABAHAH GOLD FINANCING PRACTICE IN ACEH WITH REFERENCE TO ISLAMIC BANKING AND SHARIA PAWNSHOP - Khalil, Munawar; Ismaulina, Ismaulina (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2022)
Abstract: The purpose of the study was to determine the implementation of gold murabahah financing for Islamic banking and Sharia pawnshops, the reasons for the differences in implementation, and their suitability in the Islamic economic perspective. In principle, the implementation of financing gold murabahah of sharia banking and sharia pawnshops is similar in form. But what distinguishes it lies in the technique of contracting and the transaction of delivery of goods. For example, customers buying gold in murabahah can take the purchase gold directly without waiting for the installment to be paid off and if the gold is available, and provide collateral with other goods, but in some other Islamic banks, the goods purchased must be used as collateral so that in this Islamic banking using a double contract, namely the murabahah contract at the time of purchase of goods,  Then the rahn contract (pawn) when the goods are used as collateral. This is the same as the practice carried out by sharia pawnshops in Aceh province. As such, it can be concluded that the implementation of gold murabahah financing in Islamic financial institutions according to the Islamic economy is in accordance with Islamic economic principles.Keywords: Islamic economics, financing, murabahah, shariah banking, and sharia pownshop